Editorial - S Bhattarai (Nepal Journal of Dermatology, Venereology & Leprology)
No abstract available. DOI: http://dx.doi.org/10.3126/njdvl.v12i1.10587 Nepal Journal of Dermatology, Venereology & Leprology Vol.12(1) 2014, page i